2002
DOI: 10.1128/jvi.76.14.7276-7292.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Neoplastically Transformed Cells in Marek's Disease Herpesvirus-Induced Lymphomas: Recognition by the Monoclonal Antibody AV37

Abstract: Understanding the interactions between herpesviruses and their host cells and also the interactions between neoplastically transformed cells and the host immune system is fundamental to understanding the mechanisms of herpesvirus oncology. However, this has been difficult as no animal models of herpesvirus-induced oncogenesis in the natural host exist in which neoplastically transformed cells are also definitively identified and may be studied in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 96 publications
(95 reference statements)
6
53
0
1
Order By: Relevance
“…Previous studies demonstrated that primary MDV tumor cells have a T reg phenotype, as transformed cells were shown to express well-established markers of regulatory T cells such as CD4 and CD25 (7,36). In this study, we were able to demonstrate that vIL-8 specifically binds to CD4 ϩ CD25 ϩ T cells, which suggests that vIL-8 might recruit these cells as a target for infection and transformation.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies demonstrated that primary MDV tumor cells have a T reg phenotype, as transformed cells were shown to express well-established markers of regulatory T cells such as CD4 and CD25 (7,36). In this study, we were able to demonstrate that vIL-8 specifically binds to CD4 ϩ CD25 ϩ T cells, which suggests that vIL-8 might recruit these cells as a target for infection and transformation.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, we were able to demonstrate that vIL-8 specifically binds to CD4 ϩ CD25 ϩ T cells, which suggests that vIL-8 might recruit these cells as a target for infection and transformation. As CD25 is a component of the IL-2 receptor (IL-2R), which promotes cell proliferation and increased viability of naïve T cells, it is possible that IL-2R signaling is subverted in the initial stages of transformation and immortalization, resulting in lymphomagenesis (7). Alternatively, it is tempting to speculate that the recruited CD4 ϩ CD25 ϩ T cells have a regulatory phenotype that might suppress antitumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expression of MHC class I molecules in cells infected with MDV seems to be variable. Some studies have reported the increased expression of MHC class I molecules and the β2M gene in CEFs infected with MDV, MD lymphoma and the feather pulp of MDV-infected chickens (Abdul-Careem et al, 2008;Burgess and Davison, 2002;Morgan et al, 2001). These findings show that host responses are generated in the skin and feathers, which could be exploited as targets for developing strategies to control MDV infection in the FFE, thus limiting horizontal virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription was carried out in 20 µl with 1 µg of total RNA by using SuperScript™ III Reverse Transcriptase (Invitrogen, USA) and oligo (dT) [12][13][14][15][16][17][18] primers (Invitrogen, USA). Primers (Table 1) for quantitative real-time RT-PCR were designed by Primer3 online primer designer system (http://frodo.wi.mit.edu/).…”
Section: Rna Extraction and Quantitative Real-time Rt-pcrmentioning
confidence: 99%